Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/srep26936
|View full text |Cite
|
Sign up to set email alerts
|

Metallic glassy Zr70Ni20Pd10 powders for improving the hydrogenation/dehydrogenation behavior of MgH2

Abstract: Because of its low density, storage of hydrogen in the gaseous and liquids states possess technical and economic challenges. One practical solution for utilizing hydrogen in vehicles with proton-exchange fuel cells membranes is storing hydrogen in metal hydrides. Magnesium hydride (MgH2) remains the best hydrogen storage material due to its high hydrogen capacity and low cost of production. Due to its high activation energy and poor hydrogen sorption/desorption kinetics at moderate temperatures, the pure form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 41 publications
(73 reference statements)
1
38
0
Order By: Relevance
“…Obviously, using such pressurized hydrogen gas tanks as a source of fuel in vehicles is not safe and intensive research must be dedicated to improving the structural and mechanical properties of the materials used in the manufacture of the tanks. 24 Moreover, compressed hydrogen gas systems have low volumetric hydrogen storage densities. 25 Cryo-compressed hydrogen storage (CcH 2 ) and liquid hydrogen (LH 2 ) storage are alternative mature approaches in which hydrogen is liquidized at À253 C and compressed into vessels that can be pressurized to 250-350 atm.…”
Section: Hydrogen Storagementioning
confidence: 99%
See 2 more Smart Citations
“…Obviously, using such pressurized hydrogen gas tanks as a source of fuel in vehicles is not safe and intensive research must be dedicated to improving the structural and mechanical properties of the materials used in the manufacture of the tanks. 24 Moreover, compressed hydrogen gas systems have low volumetric hydrogen storage densities. 25 Cryo-compressed hydrogen storage (CcH 2 ) and liquid hydrogen (LH 2 ) storage are alternative mature approaches in which hydrogen is liquidized at À253 C and compressed into vessels that can be pressurized to 250-350 atm.…”
Section: Hydrogen Storagementioning
confidence: 99%
“…Metallic Mg and Mg-based materials have been considering as the most important candidate hydrogen storage materials for use in real applications. [19][20][21][22][23][24]36 The worldwide interest in Mg is attributed to its natural abundance, low cost, light weight, and its high gravimetric (7.60 wt%) and volumetric (110 g l À1 ) hydrogen storage capacities. Recently, it has been reported that waste Mg-based alloys such as Mg-Al 39 and Mg-Gd 40 were successfully used as feedstock materials to produce a good quality of MgH 2 .…”
Section: Magnesium Hydridementioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore natural to expect not only the development of new Ni-based catalysts (e.g. Ni-Zr15, ZrPdNi5) but also the replacement of known noble-metal-based catalysts by reliable Ni and Ni-based analogs.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen is an energy carrier, which holds tremendous promise as a new clean energy option23. It is a convenient, safe, versatile fuel source that can be easily converted to a desired form of energy without releasing harmful emissions45. A key advantage of hydrogen is that when burned, carbon dioxide (CO 2 ) is not produced.…”
mentioning
confidence: 99%